Dos fundamentos à teoria da convenção em Jean-Jacques Rousseau - Abreu, Wilame Gomes de (2019)
This research comprises the foundations that make up the formulation and explanation of the theory of the convention in the political works of Jean-Jacques Rousseau, whose philosophical approach delineates in the ethico-political scope. The main objective of this thesis is to investigate the foundations of political thought from the conditions of possibility and validity in the theoretical-practical field with the purpose of explaining the formulation of the theory of the convention in Jean-Jacques Rousseau. So that, from the point of view of the problematization, the research that resulted in this systematization was motivated by the fact that the formulation and explanation of the convention locates its thread in an ontological foundation. Is it possible to project philosophical studies of such obvious rational data? It has been accepted since Galileo that unanswered questions are not intelligent, precisely because it contains no possible answers. What is the stimulus if they seem so obvious or feasible? The fact is, properly, the supposition that the social order results only from a convention; that convention is not a reality derived from nature, but only an act of human will, whose possible occurrence is made by the convergence of interests. There are, then, two problems, one unfolds in the other, so that the first refers to the foundations of convention, and the second responds to the formulation of convention theory. First, how is convergence of interests possible for the attainment of the general will within civil society? What would make a man want to agree, submit to a body other than himself? - Because? Perhaps if he had been left alone under the care of provident nature his life would be sufficiently well supplied, to whose real delivery he would have made all the necessities that we longed for outside her, apart from having no meaning for him, would have been out of his reach. Secondly, how is the convergence of interests for the attainment of the general will possible without the need to suppress the conflict of interests within civil society and their competition between individuals and parties? Thus, the objective is the formal radicality of the Contract against the factual to clarify the anthropological, psychological, historical, political and juridical foundations, to which we think to constitute as a real unit of the theory of the convention in Jean-Jacques Rousseau. It has also been sought to show that convergence of interests is possible for the attainment of the general will without the need to suppress the conflict of interests within civil society and their competition between individuals and parties. Convention as the spirit of the social order indicates that the continuity of the possible basis of conventional unity depends on the cultivation and substantial re-signification of the dignity of its components. So that the possibility of perpetuity of the obligations is conditioned to the real effectiveness of protection of the individual members of society. This leads us to infer that the duration of the body politic can be measured by the size and depth of care devoted to each of its parts.